GAMBARAN RISIKO PENYAKIT TIDAK MENULAR HIPERTENSI MELALUI PEMERIKSAAN KESEHATAN PADA MASYARAKAT DI DESA PISING KECAMATAN DONRI-DONRI KABUPATEN SOPPENG - Arimbi, Siti Nurhaliza; Tunnisa, Aulia; Bayu, Fahrul Syahisna; Khatima, Nurul; Ismail, Musdalifa; Permata, Lisda Diah; Nurlinda, Nurlinda (Media Literasi Indonesia, 2026)
Hypertension is one of the major non-communicable diseases that continues to increase and contributes significantly to morbidity and mortality rates. This community service activity aimed to describe the risk factors of hypertension among residents in Pising Village, Donri-Donri District, Soppeng Regency. The method used was a descriptive approach with total sampling technique involving 60 respondents diagnosed with hypertension. Data were collected using a structured questionnaire covering demographic characteristics, family history, salt consumption, physical activity, and smoking habits. The results showed that most respondents were aged 51–70 years, predominantly female, had low educational background, and worked as housewives. The majority of respondents had excessive salt consumption, some had a family history of hypertension, lacked regular physical activity, and a small proportion had smoking habits. These findings indicate that hypertension is influenced by both non-modifiable factors such as age, sex, and family history, as well as modifiable factors including dietary patterns, physical activity, and smoking behavior. This activity contributes to community health promotion efforts by providing evidence-based information to support preventive and promotive strategies in controlling hypertension at the community level.